Prevalence and risk factors for menstrual disorders among systemic lupus rythematosus patients - Mohd Shah, Azarisman Shah; NNA, Fatnoon; D, Zainal (Singapore Medical Association, 2008)
Introduction: This study aims to determine the prevalence and the types of menstrual disorders among patients with systemic lupus erythematosus (SLE) and to identify factors that influence their development. Methods: 61 patients with SLE were enrolled into a cross-sectional, observational study at the medical outpatient clinic, Hospital Universiti Sains Malaysia. A total of 120 healthy women were selected randomly to act as the control group. A questionnaire was administered, vital signs were recorded, and blood was evaluated for routine investigations. A review of past medical records was also undertaken. Results: The mean age and standard deviation for the study group was 33.23 +/- 10.96 years, the majority being ethnic Malays. 75 percent had a severe SLE disease activity index score on initial presentation, and 59 percent were on cyclophosphamide. 49 percent of the study population had menstrual irregularities, of which 60 percent had sustained amenorrhoea. Nine patients with sustained amenorrhoea had hormonal assays, which confirmed the diagnosis of premature menopause. Conclusion: This study showed that SLE patients had a higher risk of developing menstrual irregularities compared to the normal/healthy population. The risk was higher in the older age group (greater than 30 years old) and those on cyclophosphamide therapy, especially those with a cumulative dose of more than 10 g. Sustained amenorrhoea was the commonest irregularity and a majority of them had confirmed premature menopause.